Z-ACA allotrope: a topological carbon material with obstructed Wannier charge center, real topology, and hinge states - Wu, Lunsheng; Li, Yang (Frontiers in Physics, 2024)
As the most prevalent element on our planet, carbon manifests a wide variety of allotropic phases, significantly contributing to its complex physical properties. Recently, several carbon allotropes have been reported to possess abundant topological phases in theory and experiment. This work focuses on a sp3 carbon allotrope, Z-ACA allotrope, which consists of 5-6-7-type Z-ACA carbon rings. This allotrope has been reported previously as a superhard material comparable to diamond. In this study, we report that it is a candidate for both an obstructed atomic insulator and a real Chern insulator. It is worth mentioning that Z-ACA exhibits an unconventional bulk-boundary correspondence due to its hinge boundary state manifestation. Our current research indicates that Z-ACA is a suitable carbon phase platform for studying the real topology and second-order bulk-boundary correspondence.